Education in the Waiting Room: Description of a Pediatric Emergency Department Educational Initiative. Issue 10 (October 2017) - Reid, Sarah; Neto, Gina; Tse, Sandy; Farion, Ken J.; Marvizi, Ariyan; Smith, Lauren; Clarkin, Chantalle; Rohde, Kristina; Moreau, Katherine
Abstract : Objective: The aim of this study was to understand parents' awareness of and reactions to a slide presentation based waiting-room educational initiative. Methods: This was a prospective observational study at a Canadian tertiary-care pediatric emergency department (ED) with an annual census of 68, 000 visits. An anonymous parental survey was developed de novo, and parents were asked to complete the survey during their low-acuity ED visit over a 2-week study period. Descriptive statistics were used to describe responses and themes. Results: Parents completed 520 surveys (733 approached, 70.9% response rate). Eighty-three percent of respondents had previously sought care in the ED. Most parents (68.9%) were aware of the slide presentation, but only 33.7% were able to watch it in its entirety (20 minutes' duration). Of those who watched the whole presentation, 62.9% understood that lower-acuity cases are assessed in the ambulatory zone of the ED, and sicker children are assessed in the acute zone (89.4%), 79.9% felt the presentation helped them to understand how the ambulatory zone functions, and 83.2% appreciated the current wait-time information. General questions about common health concerns were answered correctly in 58.3% (fever), 56.0% (gastroenteritis), 50.5% (abdominal pain/constipation), 35.7% (earache), and 17.0% (head injury). Conclusions: The majority of parents were aware of this waiting-room educational initiative, but there was variable uptake of information. Parents watching the entire presentation appreciated the information provided, especially wait-time information, and felt it improved their experience. Knowledge of common health conditions was low; novel methods of knowledge transfer must be utilized and evaluated.